Evaluation of varian ix clinical linear accelerator performance based on daily quality assurance using quickcheck phantom - Yusniman, Nurul Afiqah (Universiti Sains Malaysia, 2025)
This study aims to evaluate the performance consistency of the Varian iX Clinical Linear Accelerator (LINAC) by analysing radiation output parameters using the PTW QUICKCHECK Phantom during daily quality assurance (QA) procedures at Hospital Pakar Universiti Sains Malaysia (HPUSM). The parameters measured include central axis dose (CAX), beam flatness, symmetry in the gantry-target (GT) and left-right (LR) directions, and beam quality factor (BQF) for photon (6 MV) and electron beams (6, 9, 12, and 15 MeV). Data were collected over a three-month period from January to March 2025. All measurements were taken using a 10 × 10 cm² field size with 100 MU delivered at a dose rate of 300 MU/min. Repeated measurements were conducted in cases of reading errors, and any invalid data were excluded from the analysis. The results showed that all radiation output parameters remained within the tolerance limits recommended by AAPM TG-142 (±3%), indicating excellent output stability and machine performance. This confirms the suitability of the QUICKCHECK device as a reliable and efficient tool for routine daily QA in radiotherapy settings.